Geography and history lessons at museum and archive - Lajh, Andreja; Konečnik Kotnik, Eva (Journal for Geography, 2021)
Geography and history lessons at museum and archive The article presents some characteristics of teaching in museums and archives and highlights the positive effects of such teaching on pupils and students. The results of the analysis of pedagogical contents offered to school groups by Slovenian museums and archives are described, which show that both museums and archives are well aware of their educational tasks and also carry them out regularly. A presentation of the results of a pedagogical experiment is included, in which we tested one of the author’s innovative pedagogical workshops in the museum, in which we wanted to highlight the correlation of content, goals and competencies of geography and history. With the results, we proved that this form of teaching had a positive effect on the development of knowledge in the experimental sample of students and that it was the motivation in the extracurricular institution that motivated them.